QSAR Studies of Some 4-(Substituted)-Phenoxy-2-(4-Methyl-1-Piperazinyl) Quinazolines as Anticonvulsive Agents - K. Jain, Sanmati (Asian Journal of Chemistry, 2010)
4-(Substituted)-phenoxy-2-(4-methyl-1-piperazinyl)quinazolines are reported to possess anticonvulsive properties. Therefore, QSAR studies were undertaken so as to evaluate the influence of the various physicochemical parameters on their biological activity, taking negative logarithmic value of effective dose (log 1/ED50) as dependent and different physicochemical and structural parameters (log P, MR and Dip-X) as independent variables. The results indicate that dipole moment (Dip-X, electronic factor) and log P (hydrophobic factor) contribute significantly in imparting the biological activity (R = 0.85, F = 10.39, R2cv =0.629).